Assessment and comparison of bacterial load levels determined by quantitative amplifications in blood culture-positive and negative neonatal sepsis - Stranieri, Inês (2018)
Bacterial sepsis remains a major cause of mortality and blood cultures are the gold standard of laboratory diagnosis even though they lack sensitivity in neonates. Culturenegative sepsis, also known as clinical sepsis, has long been considered a diagnosis in neonatal intensive care units because, as well as culture-positive infants, culture-negative neonates have worse prognosis in comparison with non-infected ones. Quantitative amplifications are used to detect bacterial infections in neonates but results are considered only in a qualitative way (positive or negative). The aim of the present study was to determine and compare bacterial load levels in blood culture-positive and culture-negative neonatal sepsis. Seventy neonates with clinical and laboratory evidence of infection admitted at three neonatal intensive care units were classified as blood culture-positive or culture-negative. Blood samples obtained at the same time of blood cultures had bacterial load levels assessed through a 16S rDNA qPCR. Blood cultures were positive in 29 cases (41.4%) and qPCR in 64 (91.4%). In the 29 culture-positive cases, 100% were also positive by qPCR, while in the 41 culture-negative cases, 35 (85.4%) were positive by qPCR. Bacterial load levels were in general < 50 CFU/mL, but were significantly higher in culture-positive cases (Mann-Whitney, p = 0.013), although clinical and laboratory findings were similar, excepting for deaths. In conclusion, the present study has shown that blood culture-negative neonates have lower bacteria load levels in their bloodstream when compared to blood culture-positive infants.